Low Temperatures Influence the Preservation of Regenerative Properties of Hyaluronic Acid with Different Molecular Weight - Seliuta, Anatolii; Nardid, Eduard; Polyakova, Anna; Gurina, Tetiana (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):291